Human rights in the United States : beyond exceptionalism - Hertel, Shareen; Libal, Kathryn, 1968- (Cambridge ; New York : Cambridge University Press, 2011)
"This book brings to light emerging evidence of a shift toward a fuller engagement with international human rights norms and their application to domestic policy dilemmas in the United States. The volume offers a rich history, spanning close to three centuries, of the marginalization of human rights discourse in the United States. Contributors analyze particular cases of U.S. human rights advocacy aimed at addressing persistent inequalities within the United States itself, including advocacy on the rights of persons with disabilities; indigenous peoples; lone mother-headed families; incarcerated persons; lesbian, gay, bisexual, and transgendered people; and those displaced by natural disasters, most notably Hurricane Katrina. The book also explores key arenas in which legal scholars, policy practitioners, and grassroots activists are challenging multiple divides between "public" and "private" spheres (for example, in connection with children's rights and domestic violence) and between "public" and "private" sectors (specifically, in relation to healthcare and business and human rights)"--
Machine generated contents note: Foreword: are Americans human? reflections on the future of progressive politics in the United States Dorothy Q. Thomas; 1. Paradoxes and possibilities: domestic human rights policy in context Kathryn Libal and Shareen Hertel; Part I. Structuring Debates, Institutionalizing Rights: 2. The yellow sweatshirt: human dignity and economic human rights in advanced industrialized democracies Rhoda E. Howard-Hassmann; 3. The welfare state: a battleground for human rights Mimi Abramovitz; 4. Drawing lines in the sand: building economic and social rights in the United States Cathy Albisa; 5. State and local commissions as sites for domestic human rights implementation Risa Kaufman; Part II. Challenging Public/Private Divides: 6. The curious resistance to seeing domestic violence as a human rights violation in the United States Sally Engle Merry and Jessica Shimmin; 7. At the crossroads: children's rights and the U.S. government Jonathan Todres; 8. Entrenched inequity: healthcare in the United States Jean Connolly Carmalt, Sarah Zaidi, and Alicia Ely Yamin; 9. Business and human rights: a new approach to advancing environmental justice in the United States Joanne Bauer; Part III. From the Margins to the Center: Making Harms Visible through Human Rights Framing:10. The law and politics of U.S. participation in the UN convention on the rights of persons with disabilities Michael Ashley Stein and Janet E. Lord; 11. The anomaly of citizenship for indigenous rights Bethany R. Berger; 12. Human rights violations as obstacles to escaping poverty: the case of lone mother-headed families Ken Neubeck; 13. The human rights of children in conflict with the law: lessons for the U.S. human rights movement Mie Lewis; 14. LGBT rights as human rights in the United States: opportunities lost Julie Mertus; 15. No shelter: disaster politics in Louisiana and the struggle for human rights Davida Finger and Rachel E. Luft.
Includes bibliographical references and index.
Keywords: Human rights -- United States; POLITICAL SCIENCE / Political Freedom & Security / Human Rights